A consideration of the explicit and implicit messages about social mobility in Damian Hind's speech (31st July 2018). Issue 2 (3rd April 2019) - Carpenter, Chris
ABSTRACT: Social Mobility (SM) has been a feature of much government educational policy in recent times (Payne 2017) although parties tend to argue over which of them has the most 'natural' identification with it. Over time various education secretaries from David Blunkett (Labour Education Secretary from 1997 to 2001) through to Justine Greening (Conservative Education Secretary 2016–2018) have all made SM a central theme in their educational policy messages. More recently this was taken up by Damian Hinds (Education secretary from 2018 to present time) in a speech to the Resolution Foundation in July 2018. In this paper, the key messages in Hinds speech will be subjected to scrutiny and it will be argued that in the speech Hinds offers a limited version of Social Mobility. Also, that implicitly, the kinds of social democratic values that might seem to naturally be an inherent part of social mobility have been 'hollowed out' and replaced with values that are more redolent of free-market principles.